(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The low level of Islamic financial literacy in Indonesia is still a serious problem, with the literacy index only reaching 39.11% based on the National Survey of Financial Literacy and Inclusion (SNLIK) 2024. This disparity shows the need for intensive education, especially to the younger generation. To address this challenge, the Community Service Program (KKN) team from Fatmawati Soekarno State Islamic University (UIN) Bengkulu conducted socialization and education activities on Islamic banking for students of SMK Negeri 1 Bengkulu City. This activity uses a Participatory Action Research (PAR) approach, which emphasizes active participation between students and school parties in all stages of the activity. Socialization is carried out through interactive methods such as material delivery, discussion, case studies, and post-test evaluation. The results of the activity showed that more than 80% of the participants understood the basic concepts of Islamic banking and its products, and were able to distinguish between Islamic and conventional systems. In addition, 85% of participants were satisfied with the quality of the material delivery. This activity proved to be effective in improving Islamic financial literacy and is expected to be replicated in other schools as a concrete step to strengthen the Islamic economic ecosystem in Indonesia. Keywords: Islamic financial literacy, Islamic banking, socialization, students, community service ABSTRAK Rendahnya tingkat literasi keuangan syariah di Indonesia masih menjadi permasalahan serius, dengan indeks literasi hanya mencapai 39,11% berdasarkan Survei Nasional Literasi dan Inklusi Keuangan (SNLIK) 2024. Ketimpangan ini menunjukkan perlunya edukasi yang intensif, khususnya kepada generasi muda. Untuk menjawab tantangan tersebut, tim Kuliah Kerja Nyata (KKN) dari Universitas Islam Negeri (UIN) Fatmawati Soekarno Bengkulu melaksanakan kegiatan sosialisasi dan edukasi mengenai perbankan syariah kepada siswa SMK Negeri 1 Kota Bengkulu. Kegiatan ini menggunakan pendekatan Participatory Action Research (PAR), yang menekankan partisipasi aktif antara mahasiswa dan pihak sekolah dalam seluruh tahapan kegiatan. Sosialisasi dilakukan melalui metode interaktif seperti penyampaian materi, diskusi, studi kasus, dan post-test evaluasi. Hasil kegiatan menunjukkan bahwa lebih dari 80% peserta memahami konsep dasar perbankan syariah dan produk-produknya, serta mampu membedakan antara sistem syariah dan konvensional. Selain itu, 85% peserta merasa puas terhadap kualitas penyampaian materi. Kegiatan ini terbukti efektif dalam meningkatkan literasi keuangan syariah dan diharapkan dapat direplikasi di sekolah lain sebagai langkah konkret memperkuat ekosistem ekonomi syariah di Indonesia. Kata Kunci: literasi keuangan syariah, perbankan syariah, sosialisasi, siswa, pengabdian Masyarakat